THE EFFECTIVENESS OF POLICY PROHIBITION OF THROWING WASTE INTO THE RIVER IN BABAKANPARI VILLAGE, CIDAHU DISTRICT, SUKABUMI REGENCY - Dina Siti Astuti; Dian Purwanti; M. Rijal Amirulloh (DIA: Jurnal Administrasi Publik, 2022)
In the Peraturan Daerah Kabupaten Sukabumi Nomor 13 Tahun 2016 concerning Waste Management and Retribution for Waste/Hygiene Services Subsection 26 Verse f regarding the prohibition of throwing waste into the river, it turns out that it is still violated by several communities in Babakanpari Village, Cidahu District, Sukabumi Regency. The purpose of this study was to determine the effectiveness of the policy of banning waste into the river in Babakanpari Village, Cidahu District, Sukabumi Regency. To find out the effectiveness of the policy of prohibiting waste disposal in Babakanpari Village, Cidahu District, researcher uses a theory from Richard E. Matland which stated "four appropriate" that must be met in terms of policy effectiveness, that are policy accuracy, implementation accuracy, target accuracy, and environmental accuracy. The results showed that the policy of prohibiting throwing waste into the river in Babakanpari Village, Cidahu District, Sukabumi Regency, was appropriate, the government has also tried to give an appeal to the community not to throw waste into the river. However, in its implementation, the sanctions given to people who violate the policy cannot be in accordance with what is in the Regional Regulation.